2020
DOI: 10.1007/s12237-020-00722-3
|View full text |Cite
|
Sign up to set email alerts
|

Copepod Assemblage Dynamics in a Snowmelt-Dominated Estuary

Abstract: What limits secondary production in the estuaries of snowmelt-dominated basins? Due to substantial differences in their annual hydrographs, zooplankton dynamics in these estuaries are expected to differ from better-studied pluvial systems. We hypothesized that water residence time limited zooplankton production in the undammed, snowmelt-dominated estuary of the Fraser River, Canada. We sampled zooplankton and associated environmental variables bi-weekly to monthly in slough and channel areas of the estuary ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 127 publications
(160 reference statements)
0
2
0
Order By: Relevance
“…Many estuaries have sustained severe losses of habitats such as tidal wetlands and terminal sloughs (Brophy et al, 2019; Whipple et al, 2012). These estuarine habitats, characterized by high light availability and longer residence times, often support higher primary and secondary productivity than deeper or more turbulent areas (Ahearn et al, 2006; Bukaveckas et al, 2011), where phytoplankton are limited by access to the photic zone and both phytoplankton and zooplankton biomass is rapidly advected or dispersed (Breckenridge et al, 2020). Shallow, productive habitats can subsidize adjacent areas with lower in situ production (Lopez et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Many estuaries have sustained severe losses of habitats such as tidal wetlands and terminal sloughs (Brophy et al, 2019; Whipple et al, 2012). These estuarine habitats, characterized by high light availability and longer residence times, often support higher primary and secondary productivity than deeper or more turbulent areas (Ahearn et al, 2006; Bukaveckas et al, 2011), where phytoplankton are limited by access to the photic zone and both phytoplankton and zooplankton biomass is rapidly advected or dispersed (Breckenridge et al, 2020). Shallow, productive habitats can subsidize adjacent areas with lower in situ production (Lopez et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This may be an indication that predominantly estuarine species cannot easily undergo long-distance dispersal across oceans. In different parts of the world such as India (Madhu et al, 2007;Rakhesh et al, 2013;Paul et al, 2019), Europe (Vieira et al, 2003), Africa (Kibirige and Perissinotto, 2003;Froneman, 2004;Carrasco and Perissinotto, 2015;Ounissi et al, 2016), America (Krumme and Liang, 2004;Araujo et al, 2008;Howson et al, 2017;Salvador and Bersano, 2017;Breckenridge et al, 2020), and Oceania (Rose et al, 2020), it has been shown repeatedly that differences in the composition of the dominant copepod fauna in estuaries increase with distance. The abundance and diversity of zooplankton communities showed spatial, seasonal, and interannual trends in Barnegat Bay (Howson et al, 2017), and also in the Paranagua estuary (Salvador and Bersano, 2017).…”
Section: Copepods In Estuariesmentioning
confidence: 99%